ANALYSIS OF TRANSPORT SYSTEM PERFORMANCE INDICATORS - Komilov A. A. (Journal Park Publishing, 2023)
The main purpose of this study is to comprehensively analyze the performance indicators of the transport system. By evaluating various key performance indicators, it is possible to gain a deeper understanding of the system's operational efficiency, reliability, security, and overall industry performance.
Keywords: transport, efficiency indicators, analysis.